2008
DOI: 10.1521/suli.2008.38.4.456
|View full text |Cite
|
Sign up to set email alerts
|

Attempted Suicide Among Iranian Population

Abstract: Predictors of suicide attempts in Iran, to distinguish any similarities and differences of these predictors between suicide attempts in Iran and other developed and developing countries and to investigate the relation between general psychiatric symptoms and repetition of suicidal attempts were assessed. The validated Farsi version of the General Health Questionnaire-28 (GHQ-28) was used to assess multiple dimensions of quality of life of suicide attempters as depression, anxiety, social dysfunction, and somat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In this review, we also observed a suggested lower prevalence of psychiatric disorders in studies that included fewer males than females. There were very few studies that reported on sex specific prevalence rates, and whilst some supported our findings of a higher rate in males [121,135], others did not [91,102,117,121,135,148,151,160].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this review, we also observed a suggested lower prevalence of psychiatric disorders in studies that included fewer males than females. There were very few studies that reported on sex specific prevalence rates, and whilst some supported our findings of a higher rate in males [121,135], others did not [91,102,117,121,135,148,151,160].…”
Section: Discussionsupporting
confidence: 76%
“…There were, however, only 8 studies that presented sex stratified prevalence of psychiatric morbidity from India, China, and Iran [91,102,117,121,135,148,151,160]. Two studies reported a higher prevalence of psychiatric morbidity in males than females [121,135], one reported a higher prevalence in females [117], and the remaining 5 studies reported no differences [91,102,148,151,160]. Studies that used a clinician’s diagnosis of psychiatric morbidity reported a higher prevalence of anxiety related disorders (15%, 95% CI 11%–19%) than those that used a validated diagnostic interview (8%, 95% CI 7%–10%).…”
Section: Resultsmentioning
confidence: 99%
“…Further supporting this results, studies from high income settings also have found strong positive associations between divorce rate and suicide demonstrating the impact of social well-being on suicide [ 42 , 57 ]. In Iran, this has been harder to demonstrate, as divorce rate is very low compared to western countries and divorcees who attempt suicide are in low numbers [ 19 , 58 , 59 ]. The increasing temporal trend in suicide rate in Iran has shown an association with increasing divorce rate, which, supports known theories.…”
Section: Discussionmentioning
confidence: 99%
“…This finding can potentially be explained by the increasing prevalence of mental disorders, rising unemployment rates13 45 and an increasing trend in divorce rates13 in the provinces with higher HDI, such as Tehran, the capital city of Iran.…”
Section: Discussionmentioning
confidence: 99%